DEVELOPMENT OF APPROACHES TO THE ESSENTIAL CHARACTERIZATION OF THE ENVIRONMENTAL FINANCIAL POLICY - LABENKO, Oleksandr; KLYMENKO, Maksym (Scientific journal «World of Finance», 2025)
Вступ. Курс на реалізацію стратегії збалансованого природокористування у межах “зеленої” економіки потребує усвідомленого, системного державницького підходу. В основі реалізації екологічних інтересів держави лежить фінансова політика природокористування. Верифікація існуючих підходів до понятійної бази фінансової політики природокористування відсутня, що й обумовлює актуальність наукового дослідження. Мета – систематизувати концептуальні підходи та сформулювати сутнісні характеристики фінансової політики природокористування як складової фінансової політики держави. Результати. Систематизовано підходи до тлумачення фінансової політики як економічного поняття та на основі цього сформульовано сутнісні характеристики фінансової політики природокористування. Концептуально визначено, що фінансова політика природокористування є складовою державної фінансової політики, тому їй притаманні відповідні загальні сутнісні характеристики і, водночас, спеціальні, обумовлені цільовим спрямуванням – обслуговування фінансових потреб сфери природокористування. Висновки. Фінансова політика є системним поняттям, від правильного тлумачення якого залежить формування принципів, функцій, механізмів, інструментарію її реалізації. Обґрунтовано необхідність системного групування ознак фінансової політики відповідно до визначених підходів. На основі цієї концептуальної позиції виокремлено комплексний(адитивний), процесний, цільовий, функціональний підходи до сутнісного наповнення поняття “фінансова політика”. Introduction. The course towards implementing a strategy for balanced natural resource use within the framework of a “green” economy requires a conscious, systematic state approach. This includes both regulatory support and the execution of mechanisms to ensure financial resources for environmental programs. At the core of realizing the state’s ecological interests lies the financial policy for natural resource management. However, currently, despite a well-developed conceptual framework for financial policy, there is no substantiated theoretical and methodological foundation for financial policy in natural resource management that takes into account the fundamental principles of neo-institutional theory. There is also a lack of verification of existing approaches to the conceptual framework of financial policy in natural resource management, which underscores the relevance of this scientific study. The purpose of the article is to systematize and develop conceptual approaches and to formulate the essential characteristics of financial policy in natural resource management as a component of the state’s financial policy. Results. The approaches to interpreting financial policy as an economic category have been systematized, and based on this, the essential characteristics of financial policy in natural resource management have been formulated. It has been conceptually defined that financial policy in natural resource management is a component of the state’s financial policy; therefore, it possesses corresponding general essential characteristics and, at the same time, specific ones determined by its targeted orientation – servicing the financial needs of the natural resource management sector. Conclusions. The research findings demonstrate that financial policy is a systemic category, the correct interpretation of which is crucial for the formation of principles, functions, mechanisms, and tools for its implementation. The opinions of scholars regarding the essential content of financial policy have been examined and systematized. The necessity of systematic grouping of the characteristics of financial policy according to various approaches has been substantiated. Based on this conceptual position, comprehensive (additive), process-oriented, goal-oriented, and functional approaches to the essential content of the category “financial policy” have been identified.